Blast disease and wheat production in Brazil - Gisele Abigail Montan Torres; Jéssica Rosset Ferreira; Eliseu Binneck; João Leodato Nunes Maciel; Luciano Consoli (Pesquisa Agropecuária Brasileira, 2022)
Abstract This review paper presents the current context of wheat production in Brazil, the management strategies to reduce yield losses due to blast, and the biotechnological approaches to improve wheat resistance. Wheat blast or brusone is caused by the Magnaporthe oryzae Triticum (MoT) pathotype fungus that can infect all the aboveground parts of the plant. The main symptom of the blast disease is spike bleaching that impairs grain production, causing yield losses up to 100% in susceptible wheat cultivars. The first world report of blast in wheat spikes was in Brazil, in 1985, and, currently, the disease is the main constraint to wheat cultivation in tropical and subtropical areas of the Cerrado and Mata Atlântica biomes. For a long time, the use of fungicides has been found to be ineffective under high-pressure disease conditions. However, recent works have pointed out that fungicide efficiency depends on the integration of other control measures, particularly the choice of cultivars with moderate resistance. In this review paper, the high variability of wheat reaction to MoT is presented, as well as a panel of resistant or moderately resistant cultivars (including non-2NS carriers), promptly available for cultivation in regions where blast is endemic.